Salvianolic acid B inhibits autophagy and activation of hepatic stellate cells induced by TGF-β1 by downregulating the MAPK pathway - Jiang, Na; Zhang, Jing; Ping, Jian; Xu, Lieming (Frontiers in Pharmacology, 2022)
In liver fibrosis,transforming growth factor-β1(TGF-β1) can stimulate autophagy and activation of hepatic stellate cells (HSCs). Autophagy, playing a crucial role in HSCs activation,is related to liver fibrosis. Increasing evidence has suggested that anti- fibrosis effects of salvianolic acid B (Sal B). Their mechanisms of action,however, remain unclear. The aim of the article is to understand the role of Sal B in HSCs autophagy in liver fibrosis. Herein,we demostrated that TGF-β1 induce led to dramatic increase in autophagosome fomation and autophagic flux in JS1 and LX2,which was mediated through the ERK,JNK and p38 MAPK cascades. TGF-β1 significantly increased the protein of autophagy and liver fibrosis,including LC3BⅡ, ATG5, α-SMA,Col.I; silencing ATG7 attenuated the protein expression of LC3BⅡ, ATG5, Col.I. Sal B inhibits JS1 autophagy and activation by inhibiting the formation of autophagosomes and autophagic flux. Sal B significantly decreased the LC3BⅡ, ATG5, α-SMA,Col.I protein expression,pretreatment with autophagy inhibitors, Chloroquine (CQ) and 3-methyladenine (3-MA)or silencing ATG7 further increase these reductions.However, pretreatment with autophagy agonist, Rapamycin (Rapa),or overexpressed ATG5 attenuated this decrease. To futher assess the important of this mechanism, the antibody chip was used to detect the change of phosphorylation protein expression of MAPK signaling pathway after treating JS1 with Sal B. 11 differentially expressed proteins were verified. Sal B inhibits activation and auto- phagy of JS1 induced by TGF-β1 through downregulating the ERK, p38 and JNK signaling pathways, as demonstrated by downregulating p-ERK,p-JNK and p-p 38 MAPK protein expression. In conclusion, Sal B inhibits autophagy and activation induced by TGF-β1 of HSCs prosibly through downregulating MAPK pathway.